2019
DOI: 10.1111/jocd.12908
|View full text |Cite
|
Sign up to set email alerts
|

A 10% Lactobionic acid‐containing moisturizer reduces skin surface pH without irritation—An in vivo/in vitro study

Abstract: Summary Background/Objectives Stratum corneum acidification is a newer strategy in management of inflammatory dermatoses; acidifying emollients are normally used for that purpose. However, a decrease in pH of the skin is commonly connected to an increase in irritation. The aim of this study was to investigate whether lactobionic acid (LA), cosmeceutical active and "superacid" belonging to the class of alpha‐hydroxy acids (AHAs), could decrease pH of skin surface without irritation. Methods Safety profile of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…In a recent study, Lukic et al have shown that topical products could induce skin acidification and that the effect is not in direct reciprocity to a products' pH, although this depends on the presence of ingredients which are proton donors and on the activity of a skin buffering system [140]. Due to numerous difficulties related to the formulation of topical products with such actives, investigations in this field are still drawing great attention in relation to the development of stabile and safe products with rather low pH [87,140,141]. Undoubtedly, research in this area should be deepened by the interlinking efficacy of these products with skin pH formation, maintenance and acid microdomains.…”
Section: Skin Health Maintenancementioning
confidence: 99%
“…In a recent study, Lukic et al have shown that topical products could induce skin acidification and that the effect is not in direct reciprocity to a products' pH, although this depends on the presence of ingredients which are proton donors and on the activity of a skin buffering system [140]. Due to numerous difficulties related to the formulation of topical products with such actives, investigations in this field are still drawing great attention in relation to the development of stabile and safe products with rather low pH [87,140,141]. Undoubtedly, research in this area should be deepened by the interlinking efficacy of these products with skin pH formation, maintenance and acid microdomains.…”
Section: Skin Health Maintenancementioning
confidence: 99%
“…An increase in the pH-value can give rise to an alteration of normal skin physiology and thus affect its barrier function among others, facilitating the growth of pathogenic bacteria that play a major part in skin conditions such as atopic eczema. 16 Interestingly, no significant differences with regard to the prevalence of skin irritations and the dropout rates could be observed between participants with a positive versus a negative medical history for atopic eczema. In other words, our study provided no evidence that individuals with a sensitive skin type (such as atopic skin) were at a greater risk for developing skin irritations than participants without atopic skin when using the two preparations being evaluated.…”
Section: Discussionmentioning
confidence: 85%
“…Intertriginous and damp skin areas such as the armpits have a slightly higher pH‐value. An increase in the pH‐value can give rise to an alteration of normal skin physiology and thus affect its barrier function among others, facilitating the growth of pathogenic bacteria that play a major part in skin conditions such as atopic eczema 16 …”
Section: Discussionmentioning
confidence: 99%
“…Beside their antioxidant activity, these bioactive substances might effectively moisturize the skin and regulate barrier function and skin pH values, which all lead to improvement of general condition and appearance of healthy skin 6,10,11 . In addition, stability, safety, and efficacy of these bioactive substances from plant extract is in line with the current needs and expectations of modern consumers/users 1,6,8,10‐15 …”
Section: Introductionmentioning
confidence: 96%